A REPRESENTAÇÃO DA INFÂNCIA NA POESIA DE AUGUSTO DOS ANJOS - SILVA, GRACIELLE ANGELINE TAVARES DA (2021)
This work aims at investigating the representation of childhood in the poetry of the Paraíba’s author Augusto dos Anjos, by analyzing some poems which are part of the book Eu e Outras Poesias, (Mágoas, Senectude Precoce, Debaixo do Tamarindo and Poema Negro) and by confronting, through a dialogical reading, the different conceptions of the children’s literature universe in Brazilian Modern Literature, specifically in a period marked by profound social, political, economic and cultural transformations in Brazil and in Europe; such changes make part of the Belle Époque. In order to do so, the adopted research methodology was that of literature revision, highlighting the following authors: Viana (1984), Helena (1984), Andrade & Filho (2004), responsible, for the most part, for this work’s literary criticism. Other referenced authors were Neto (2011), Franco (2000) and Helena (1984), calling attention to the biographism1 problem, often used to analyze Augusto dos Anjos’ works and which attributes to him impressionism traces, granting him denominations such as “the poet of death”, “the damned poet”, “the poet of bad taste”, among similar titles. This ends up creating, in a certain sense, a reductionism to Augusto dos Anjos’ literary construction. In this way, other approaches to his poetry, such as the childhood thematic, go unnoticed, because critics concentrate more on the Paraíba’s author pessimism. To discuss the childhood thematic in Augusto dos Anjos, we highlight the childhood as a symbol, marked by multiple heterogeneities between the particular and universal “I” in Augusto dos Anjos’ works, through the lenses of a psychoanalytic having Freud and Lacan as the theoretical references. Amongst these elements, it was possible to perceive the presence of amazement, of poeticism, of longing for times past, of melancholy, of sadness, of bitterness and of ludic aspects, revealing a poetry marked by memorialist characteristics. From the analyzed poetry, it was possible to verify, particularly due to the poet’s meaning plurality, that childhood in Augusto dos Anjos’ poetry would occupy a kind of privileged space while, at the same time, being conscient of the suffering brought by the memory of the lyrical I. Such memory is correlated to the idea of the lost object, as defended by Freud. In Augusto dos Anjos poetic style, this promotes the constant presence of signs and symbols referencing an unretrievable memory, leading the lyrical I to realize its own insignificance when faced with world experiences. In this sense, through means of psychoanalytical concepts, we also attempt to demonstrate that the emerging childhood in the poems of Augusto dos Anjos represents a breaking with the idea of chronological linearity, presenting a close relation with the experience. In this relation, the poet does not evoke the rescuing of a merely biographical past marked by longing for gone times and the rekindling of his existential poetic roots, but instead he evokes mainly the image of a childhood that was not necessarily happy, characterized by the usage of poetic language as a resource to look for his lost object and to incorporate said item to his very being, aiming at filling an empty space.